2013
DOI: 10.4236/ojce.2013.32a001
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Amino Alcohols as Corrosion Inhibitors in Reinforced Concrete

Abstract: The objective of this paper is to investigate the behaviour of amino alcohol corrosion inhibitors when they are used in reinforced cement mortars either as admixtures in the cement paste or as coating applications on the surface of the rebars. The reinforced cement mortars were exposed to both partial and full immersion in 3.5 wt% NaCl solution. Electrochemical measurements such as half-cell potential and linear polarization technique, as well as weight loss of the embedded rebars were performed in order to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
(25 reference statements)
0
8
0
3
Order By: Relevance
“…Deanol has been used for corrosion prevention in concrete with mixed results. [4][5][6][7] The compound adsorbs through concrete resulting in the formation of a complex precipitate of protective film, which adsorbs onto the metal surface. This provides an impenetrable barrier to metal dissolution that acts to stifle cathodic and or anodic electrochemical corrosion reactions taking place at the metal/solution interface.…”
Section: Introductionmentioning
confidence: 99%
“…Deanol has been used for corrosion prevention in concrete with mixed results. [4][5][6][7] The compound adsorbs through concrete resulting in the formation of a complex precipitate of protective film, which adsorbs onto the metal surface. This provides an impenetrable barrier to metal dissolution that acts to stifle cathodic and or anodic electrochemical corrosion reactions taking place at the metal/solution interface.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens are then cured in potable water for 20 days. After normal curing period the specimens are shifted to saline tank containing 3.5 % NaCl solution for further curing [10]. This is done so the chloride ions will penetrate the concrete surface reaching for the steel bars thereby initiating corrosion.…”
Section: Casting and Curing Of Specimensmentioning
confidence: 99%
“…The inhibitive action of steel with calcium nitrite is as follows [1,10]: [1,10,15,27,33]. But, at the same time, possible increase of corrosion rate in case of low dosage or the presence of cracks [16]. Also, increase in dosage resulted in a decrease of the setting time and lowers the compressive strength of concrete and corrosion process may get accelerated [10,32].…”
Section: Effect Of Anodic Cathodic and Mixed Inhibitors In Concretementioning
confidence: 99%
“…It has been reported that carboxylate and amino alcohol-based corrosion inhibitors show dual actions in concrete as the amines and alkanol amines adsorb on the metal surface and form a protective film against chloride [58,59], whereas the carboxylate ester compound reacts with calcium hydroxide, precipitates and blocks the pores of the concrete. This pore blocking property is said to be a secondary protection mechanism against reinforcement corrosion [16,18,44,58]. Furthermore, another study reported that some organic inhibitors adsorb better on the iron surface in the active state than in the passive state [60].…”
Section: Effect Of Organic Inhibitors In Concrete 21 Admixed Vs MImentioning
confidence: 99%